Akademi Kebidanan Di Rokan Hilir Dengan Pendekatan Arsitektur Tropis - Putra Mhd Alamsyah; Pedia Aldy; Wahyu Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Health development is one of the main factors to promote an area. If an area in the field of health is good, then the rate of progress and human resources will also improve. One factor that is still ahealth problem in Indonesia is still high mortality rate of mothers and children. This is due to the lack of public knowledge in the world of health, especially in terms of delivery was also afterpostpartum. To support the achievement of the Vision Riau Province in health in the form of "People Riau The Independent For Healthy Living In 2020.". So we need the construction ofMidwifery Academy of Rokan Hilir in order to help reduce maternal mortality and child in Indonesia, especially in the area of Rokan Hilir , Rokan Hilir Regency is a regency in Riau Province, Indonesia. The capital is located in Bagansiapiapi, historic city, and was once known asthe largest fish producer in Indonesia. The district has an area of 8,941 km² and a population of 349 771 inhabitants. Rokan Hilir is divided into 15 districts and 83 villages. Rokan Hilir Midwifery Academy is to apply the concept of building "Hierarchy second Mind" and use the theme Tropical Architecture. Using the theme of tropical architecture of the building is expected to be able to reduce the adverse effects of the hot climate of the area tropis.There is four application tropical architecture used include the distance between buildings, shading, vegetation and cross ventilation. Four the theme elements incorporated into the design of buildings that academic buildings, manager, dormitory and Hall.Keywords: Midwifery Academy, Hierarchy second Mind, Tropical Architecture.